INTELLECTUAL LAW IN IT INDUSTRY IN UKRAINE - Шуст, Наталія Борисівна; Антонюк, Анастасія Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose in the article authours are exploring the theoretical and legal aspects of legal protection of intellectual property rights; topical issues of innovative development of the economy in the country are also considered, namely, dissemination of experience and knowledge in the innovation sphere, problems of regulatory support of innovative activity and commercialization of scientific and technical developments, Ukrainian realities of protection of innovative technologies. The methodological basis of the research comprise general scientific methods of scientific knowledge, such as dialectical as well as logical techniques: analysis, comparison, generalization. Results: the authours focus on the identified the basic prerequisites and needs for the development of intellectual law in the field of information technology; identification of the problem of protection of intellectual property in Ukraine and conditions of formation of the national innovation system of Ukraine. The directions that hinder innovative development in Ukraine and the reasons that adversely affect the development of the education and science system in the field of intellectual property are substantiated. Discussion: basis of national legislation in the field of intellectual property rights, search for ways to improve the directions of development of the legal system of Ukraine; creation of new knowledge and intellectual products recognized at the state level. Оne of the main problems in the field of protection of intellectual property rights is the lack of a national innovation system, which hinders the development of innovative activity in Ukraine of highly developed intellectual property market. The problems and the current situation in the field of innovation development and law are a consequence of the lack of a strategy of transition of the Ukrainian economy to the innovative path of development, the absence of the formation of a national innovation system that would ensure its implementation.